Application of an Optimized HPLC Method for the Detection of Various Phenolic Compounds in Apples from Lithuanian Cultivars. (24th April 2014) - Liaudanskas, Mindaugas; Viškelis, Pranas; Jakštas, Valdas; Raudonis, Raimondas; Kviklys, Darius; Milašius, Arvydas; Janulis, Valdimaras
Abstract : A specific analytical procedure including sample preparation and HPLC analysis was developed and validated for the detection of phenolic compounds in the samples of different apples from popular Lithuanian cultivars "Aldas, " "Auksis, " "Ligol, " and "Šampion." The conditions for phenol extraction were optimized: the solvent of the extraction was 70% (v/v) ethanol, and the extraction was performed in an ultrasound bath for 20 min at the temperature of 40°C. The HPLC mobile phase consisted of 2% (v/v) acetic acid in water and 100% (v/v) acetonitrile. Using the HPLC technique, 11 analytes were identified, and their specificity was confirmed: procyanidin B1, (+)-catechin, chlorogenic acid, procyanidin B2, (−)-epicatechin, rutin, hyperoside, isoquercitrin, avicularin, quercitrin, and phloridzin. Chlorogenic acid was the major component in "Aldas, " "Auksis, " and "Ligol" and procyanidin B2 in "Šampion." Hyperoside and avicularin were the dominant compounds of all the identified quercetin derivatives in "Aldas" and "Auksis;" hyperoside in "Šampion;" and quercitrin in "Ligol." The total content of phenolic compounds varied from 1641.0 ± 47.9  μ g/g (cv. "Ligol") to 4291.3 ± 154.2  μ g/g (cv. "Aldas").